Single LED Beacon-Based 3-D Indoor Positioning Using Off-the-Shelf Devices - Yinan Hou; Shilin Xiao; Meihua Bi; Yuankai Xue; Wansheng Pan; Weisheng Hu (IEEE Photonics Journal)
In this paper, we demonstrate a single light-emitting diode (LED) beacon-based 3-D indoor positioning scheme by experiment and theoretical derivation, which can overcome the limitation of multiple LED beacons involved in one positioning process. Only off-the-shelf devices are employed in this scheme, such as an image sensor, a gyroscope, and a photodiode, which have been integrated in most of commercial available smartphones so that it is compatible with most of mobile terminals. Moreover, with these simple devices, we estimate the 3-D position by using the received-signal-strength (RSS) and angle-of-arrival (AoA)-based hybrid positioning algorithm. The performance of this scheme is investigated in scenarios of the ceiling-mounted and the wall-mounted LED. The corresponding results show that, by using this scheme, 7.3 cm and 67.2 cm mean positioning errors are achieved in the ceiling and the wall LED cases, respectively. Therefore, this scheme may be considered as one of the competitive indoor positioning candidates in the future.